Utilization of Traditional Games in Maros Regency as an Ethnomathematics-Based Mathematics Learning Media - Nirfayanti; M. Asfar Abdul Majid; Hukma Gaffar (Pendidikan Matematika UNIMOR, 2025)
Ethnomathematics is a mathematical concept integrated in a culture. The presence of mathematics related to cultural elements can make a significant contribution to the mathematics learning process. This study aims to identify and analyze the use of traditional games in Maros Regency as a medium for ethnomathematics-based mathematics learning. This research is relevant because traditional games contain mathematical concepts that can enrich students' understanding of mathematics material. This research uses a qualitative approach with the Systematic Literature Review (SLR) method. Data collection techniques were carried out through documentation, interviews and literature searches from various databases, such as Google Scholar, Scopus, and related journals. Data analysis was conducted by compiling a data matrix to identify key themes, comparing findings from various studies, and synthesizing research results. The results of this study indicate that the ethnomathematics approach through traditional games can be an effective alternative to improve the quality of mathematics learning in schools.